2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22169
|View full text |Cite
|
Sign up to set email alerts
|

Use of Supplementary Online Lecture Materials in a Heat Transfer Course

Abstract: Students are often looking for internet resources to supplement college courses. Solutions manuals for course textbooks are readily (if illicitly) available and reduce the amount of time students spend outside of class actually learning to problem-solve. At the same time, the content for many courses is readily available online in many forms-some reliable, some not. There are currently valid concerns about both of these trends; related to the ability of students to solve problems independently and the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Flipped classrooms have been previously discussed in literature [4], and their advantages have been documented. Mason et al [5] showed that flipped classrooms allowed for more material to be covered, allowed for students to perform equivalently or better than those receiving traditional instruction, and were able to adapt quickly to the technique after initial struggles.…”
Section: Introductionmentioning
confidence: 99%
“…Flipped classrooms have been previously discussed in literature [4], and their advantages have been documented. Mason et al [5] showed that flipped classrooms allowed for more material to be covered, allowed for students to perform equivalently or better than those receiving traditional instruction, and were able to adapt quickly to the technique after initial struggles.…”
Section: Introductionmentioning
confidence: 99%